ICT-Supported Innovations in Small Countries and Developing Regions Perspectives and Recommendations for International Education (Educational Communications and Technology: Issues and Innovations,, 2018)
This timely analysis brings greater clarity to the question of how ICT-supported innovations are experienced in small low- to middle-income countries and developing regions with implications for international education and development. By bringing together a group of international technologists, researchers, and scholars, this book explores the building of local capacity for educational technology policy and application in such regions and ably links theory to practice to illuminate how the issues at hand play out in professional practice. The volume offers itself as an invaluable resource by offering a salient assessment of the existent methodological and ecological challenges and constraints in developing, implementing, and evaluating technology and technology research, while simultaneously providing recommendations and strategy for future policy and implementation. Among the topics covered: The research agenda for technology, education, and development. ICT curriculum planning and development: policy and implementation lessons from small developing states. New challenges for ICT in education policies in developing countries. Playful partnerships for game-based learning in international contexts. Addressing persistent ICT-in-education challenges in small developing countries. ICT-Supported Innovations in Small Countries and Developing Regions is of significant interest to educational technology researchers, policymakers, and officials with influence over resource allocation and implementation of technology innovations. It is also relevant to administrators, teachers, instructional designers, and technology evaluators interested in advancing educational communications and technology in public and private settings.